The Legal Principle of Collateral in Fintech Lending - Trisadini Prasastinah Usanti; Anindya Prastiwi Setiawati; Ninis Nugraheni (Hang Tuah Law Journal, 2019)
Simple procedures and quick service on fintech lending gives an ease for fulfilling capital needs. Indeed, it does not require any collateral which may constrain debtors to deal with it. However, although this activity brings convenience, efficiency, quickness, and simplicity in lending services, many possible risks such as debtors’ delayed payment or even default which may burden the creditors are likely to follow as well. Without any collateral as assurance, the risks may become much higher on fintech lending as the creditor becomes a concurrent creditor who only has relatively individual rights whose position is equal to the other creditors, no droit de suite principle, and the claim is individual with general assurance.